Preparation method and application of non-specific protein adsorption resistant coating based on normal-pressure low-temperature plasma enhanced chemical vapor deposition technology
Through normal pressure and low temperature plasma enhanced chemical vapor deposition technology (PECVD) to quickly modify the ultra-thin coating against non-specific adsorption of proteins on the surface of medical devices, solving the problem of easy falling off and difficult to adapt to complex structures in the prior art, and achieving efficient and stable anti-non-specific protein adsorption effect.
Patent Information
- Application Number
- CN202411647298.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-18
AI Technical Summary
It is difficult to effectively prepare ultra-thin zwitterionic polymer coatings with high efficiency resistance to nonspecific protein adsorption and biological adhesion, especially on the surface of medical devices, the coating is prone to falling off and difficult to adapt to complex structures.
Using atmospheric low-temperature plasma enhanced chemical vapor deposition technology (PECVD), a stable, non-specific adsorption ultrathin coating on the substrate surface is rapidly modified and the organic monomers that provide positive and negative charges are free radically polymerized to form uniform covalent bond connections.
It realizes rapid modification of ultra-thin coating under normal pressure environment, significantly reduces the amount of non-specific protein adsorption, enhances the adhesion stability and adaptability of the coating, and is suitable for use on the surface of medical devices with complex structures.
Smart Images

Figure CN119529360A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of surface modification of medical devices, and in particular to a preparation method and application of a coating resistant to nonspecific protein adsorption based on atmospheric pressure low-temperature plasma enhanced chemical vapor deposition technology. Background Art
[0002] Bioattachment mainly refers to the non-specific adsorption and adhesion of proteins, cells, microorganisms, etc. on the surface of therapeutic and diagnostic equipment or other medical materials. Bioattachment can cause hemolysis, thrombosis, immune response, chronic inflammation, formation of isolation capsules on implanted devices, bacterial infection and biofilm attachment growth, etc.
[0003] Zwitterionic polymers have attracted widespread attention due to their excellent resistance to nonspecific protein adsorption and bioadhesion. Zwitterionic polymers are a type of material in which anionic and cationic groups are evenly mixed and close to electrical neutrality. Mixed ionic polymers share common characteristics and resistance to nonspecific protein adsorption and bioadhesion with traditional zwitterionic polymers. They all form energy barriers to resist nonspecific adsorption through strong hydration of ions, obtain efficient and excellent resistance to nonspecific protein adsorption and bioadhesion, and improve blood compatibility and biocompatibility. Precisely because of their strong hydration characteristics, this type of polymer exhibits strong hydrophilicity, making it difficult to form a stable and low-defect coating on the surface of medical devices. In particular, it becomes particularly difficult to prepare ultra-thin coatings of this type of strongly hydrophilic polymer with high efficiency in resistance to nonspecific protein adsorption and bioadhesion and low risk of shedding.
[0004] The commonly used preparation methods of this type of strong hydrophilic polymer coating are mainly divided into two categories: "grafting-from" and "grafting-to". "Grafting-from" is a method of growing polymers from the surface, which has the advantages of dense surface polymer layer and few defects. However, the existing methods rely on polymerization reactions in solution, which consumes a lot of monomers and solvents, has complicated reaction steps, harsh conditions, and introduces catalysts that are difficult to remove. These problems make low-cost large-scale production based on "grafting-from" very difficult. Therefore, the "grafting-to" type surface modification and coating based on this type of strong hydrophilic polymer containing anchoring functional groups is an existing method for preparing anti-nonspecific protein adsorption and bioattachment coatings on the surface of medical devices. This type of method mainly includes: 1) a method combining polymer cross-linking and surface grafting, such as zwitterionic polymers containing benzophenone groups; 2) a surface grafting method, such as zwitterionic polymers containing dopamine end groups; 3) a surface adsorption method. Surface grafting that relies on cross-linking is a more common method for zwitterionization of medical device surfaces. However, the thicker coating formed increases the possibility of shedding and further increases the risk of shedding. In addition, due to the surface tension of the solution, it is easy to accumulate in recessed areas, which is not suitable for medical devices with complex structures. The latter two often have low surface modification density or insufficient adsorption stability due to the physical structure and size of the polymer itself, which leads to poor resistance to nonspecific protein adsorption and biological attachment, making them less used in medical device surface modification.
[0005] Therefore, it is of great significance to study the preparation methods of coatings that are efficient, stable in adhesion, and have a wide range of material adaptability to resist nonspecific protein adsorption and bioadhesion. Summary of the invention
[0006] Based on this, the present invention proposes a preparation method and application of an anti-nonspecific protein adsorption coating based on atmospheric pressure low-temperature plasma enhanced chemical vapor deposition technology (PECVD). The preparation method can quickly modify a stable anti-protein nonspecific adsorption ultra-thin coating on the surface of a substrate under atmospheric pressure. The anti-protein nonspecific adsorption capacity of the modified surface refers to less than 20% of the adsorption per unit area of a tissue culture polystyrene (TCPS) sheet, and the minimum relative adsorption can be less than 1%; the rapid modification refers to a modification time of ≤300s, and the minimum modification time is only 10s; the thickness of the ultra-thin coating can be less than 200nm, and a covalent bond is formed with the substrate surface.
[0007] The present invention is achieved through the following technical scheme: a method for preparing an anti-nonspecific protein adsorption coating based on normal pressure low temperature plasma enhanced chemical vapor deposition technology, which uses organic monomers that provide positive and negative charges as raw materials, adopts a normal pressure low temperature plasma process to induce free radicalization of the organic monomers, and then polymerizes on the surface of a substrate material, and then obtains an anti-protein nonspecific adsorption coating through activation and washing.
[0008] Furthermore, the preparation method process steps include the following:
[0009] 1) Clean the base material to be coated;
[0010] 2) preparing an organic monomer solution containing allyl ester and allyl amine and charging it into a storage bottle;
[0011] 3) using compressed carrier gas to bubble through a storage bottle containing an organic monomer solution to carry the monomer to a reaction chamber containing a substrate material;
[0012] 4) Turn on the plasma power supply, adjust the voltage and gas flow, use the electric field to plasmatize the carrier gas and monomer, and diffuse them to the surface to form a polymer film;
[0013] 5) Activating by alkali or acid hydrolysis to hydrolyze the ester groups on the surface of the polymer membrane, then drying with clean compressed air and washing with pure water to obtain a coating that resists protein nonspecific adsorption.
[0014] Further, the substrate material is a water-insoluble polyurethane or nylon polymer material containing amide groups, and the substrate material is ultrasonically cleaned and dried with ethanol and ultrapure water, and / or cleaned with oxygen or nitrogen plasma. Preferably, the ultrasonic cleaning time of ethanol and ultrapure water is 15 minutes.
[0015] Furthermore, the monomers for preparing the coating layer resistant to non-specific protein adsorption and bioattachment are carried by compressed carrier gas, and the carrier gas is nitrogen and / or argon.
[0016] Furthermore, the two monomers containing allyl ester and allyl amine are mixed in a certain ratio, and allyl ester and allyl amine are organic monomers that provide negative charge and positive charge respectively, so that the surface has uniformly mixed positive and negative charges, and the amount of positive and negative charges is basically the same; the allyl ester is one or more of methyl acrylate, tert-butyl acrylate or methyl methacrylate; the allyl amine is one or more of N,N-dimethylacrylamine, N-methylacrylamine or acrylamine.
[0017] Further, the allyl-containing ester is methyl acrylate, the allyl-containing amine is N,N-dimethylacrylamine, the volume ratio of the former to the latter is 1:1 to 3:1 when nitrogen is used as a carrier gas, and the storage bottle containing the organic monomer solution is immersed in an ice water bath. Preferably, the ratio of the former to the latter is 1.7:1 to 2.2:1 when nitrogen is used as a carrier gas.
[0018] Furthermore, the plasma treatment power is 0.2 W / cm 2 -0.8W / cm 2 , the processing time is 30-120s. Preferably, the processing time is 90s.
[0019] Further, the flow rate of the nitrogen carrier gas is 0.01 m / min-1.8 m / min. Preferably, the flow rate of the nitrogen carrier gas is 0.3 m / min.
[0020] Furthermore, the substrate material after the plasma treatment is washed with ethanol to remove unfixed monomers and oligomers.
[0021] Furthermore, the hydrolysis is performed by using an inorganic strong acid or alkali, wherein the inorganic strong acid includes hydrochloric acid or sulfuric acid, and the inorganic alkali includes at least one of a sodium bicarbonate solution, a sodium carbonate solution and a sodium hydroxide solution. Preferably, a saturated sodium chloride solution containing 0.1 mol / L sodium hydroxide is used, and the hydrolysis time is 3 hours.
[0022] On the other hand, the present invention also provides an application of an anti-nonspecific protein adsorption coating based on atmospheric pressure low temperature plasma enhanced chemical vapor deposition technology on medical devices in contact with blood and tissues.
[0023] Beneficial effects of the present invention: The present invention is based on the atmospheric pressure PECVD anti-nonspecific protein adsorption and biological attachment coating preparation technology, adopts the atmospheric pressure low temperature plasma process below 100 degrees, triggers the free radicalization of organic monomers, and then polymerizes on the surface of the substrate material, and then activates and cleans to obtain the anti-protein nonspecific adsorption coating; utilizing the fast gas phase diffusion characteristics of free radicals, not only can a stable covalent connection be formed on the surface of different substrates, but also the coating is uniform, suitable for rapid ultra-thin coating preparation and complex structure surface modification, and the coating preparation of the present invention can be achieved under mild conditions, simplifying the preparation steps, making it easier to control and industrial scale processing, which is of great significance to the development of medical devices with anti-nonspecific protein adsorption capabilities. After experimental verification, the mixed ion polymer coating of the present invention can effectively reduce nonspecific protein adsorption on the surface of the substrate material. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A schematic diagram of the preparation process of the anti-nonspecific protein adsorption coating provided by the present invention;
[0025] Figure 2 It is a schematic diagram of the bacterial adsorption results of samples of Example 3 and Comparative Example 1;
[0026] Figure 3 Schematic diagram of platelet adhesion results of samples of Example 3 and Comparative Example 1. DETAILED DESCRIPTION
[0027] With reference to the above content, in order to make the technical method of the present invention clearer and more specific, specific schemes are given as examples, but it should be noted that the content protected by the application includes but is not limited to the following embodiments.
[0028] Example 1
[0029] The polyurethane film was ultrasonically cleaned with ethanol and deionized water for 15 min and dried at 60 °C for 90 min. After the material was placed in the reaction chamber, nitrogen was bubbled through a mixture of allyl esters and amines in different proportions cooled in an ice-water bath to carry the monomers into the reaction chamber. In the plasma, 0.375 W / cm 2 The membrane was treated at a power of 90 s to initiate grafting and polymerization of monomers on the membrane surface, and then washed with ethanol and deionized water for 15 min, hydrolyzed with a saturated sodium chloride solution containing 0.1 mol / L sodium hydroxide at 37°C for 3 h, washed with deionized water after the hydrolysis, and dried at room temperature for 27 h.
[0030] The relative protein adsorption test method is shown in performance test (1) relative protein adsorption test.
[0031] As shown in Table 1, compared with Comparative Example 1, the relative protein adsorption of the sample in Example 1 is significantly reduced, proving that methyl acrylate and tert-butyl acrylate can be used as negative charge sources for the mixed ion polymer coating by hydrolysis, and allylamine, N-methylallylamine and N,N-dimethylallylamine can be used as positive charge sources for the mixed ion polymer coating. The formed mixed ion polymer coating exhibits good resistance to nonspecific protein adsorption. Among them, when methyl acrylate and N,N-dimethylallylamine are used as monomers and the ratio of the former to the latter is 2:1, the best anti-nonspecific protein adsorption effect is achieved.
[0032] Table 1 Sample test results of Example 1 and Comparative Example 1
[0033]
[0034]
[0035] Example 2
[0036] The polyurethane film was ultrasonically cleaned with ethanol and deionized water for 15 min and dried at 60 °C for 90 min. After the material was placed in the reaction chamber, nitrogen was bubbled through a mixture of methyl acrylate and N, N-dimethylallylamine cooled in an ice-water bath to carry the monomers into the reaction chamber. 2 , 0.375W / cm 2 , 0.8W / cm 2 The membrane was treated at a power of 90 s to initiate grafting and polymerization of monomers on the membrane surface, and then washed with ethanol and deionized water for 15 min, hydrolyzed with a saturated sodium chloride solution containing 0.1 mol / L sodium hydroxide at 37°C for 3 h, washed with deionized water after the hydrolysis, and dried at room temperature for 27 h.
[0037] The relative protein adsorption test method is shown in performance test (1) relative protein adsorption test.
[0038] As shown in Table 2, compared with Comparative Example 1, the relative protein adsorption of the sample in Example 2 was significantly reduced, proving that the protein adsorption of the sample in Example 2 was significantly reduced after 0.2 W / cm 2 -0.8W / cm 2 After plasma power treatment, the mixed ion polymer coating was successfully modified onto the material surface, showing good resistance to nonspecific protein adsorption. 2 The best anti-nonspecific protein adsorption effect was achieved when plasma power was used for treatment.
[0039] Table 2 Sample test results of Example 2 and Comparative Example 1
[0040] sample <![CDATA[Plasma power (W / cm 2 )]]> Relative protein adsorption (%) Sample 7 0.2 17.9 Sample 8 0.375 6.99 Sample 9 0.8 13.5 Comparative Example 1 / 100
[0041] Example 3
[0042] The polyurethane film was ultrasonically cleaned with ethanol and deionized water for 15 min and dried at 60 °C for 90 min. After the material was placed in the reaction chamber, nitrogen was bubbled through a mixture of methyl acrylate and N, N-dimethylallylamine cooled in an ice-water bath to carry the monomers into the reaction chamber. 2 The membrane was treated at power of 30s, 60s, 90s, and 120s to induce grafting and polymerization of monomers on the membrane surface, and then washed with ethanol and deionized water for 15min, hydrolyzed with a saturated sodium chloride solution containing 0.1mol / L sodium hydroxide at 37°C for 3h, washed with deionized water after the hydrolysis, and dried at room temperature for 27h.
[0043] Among them, the relative protein adsorption test method can be found in Performance Test (1) Relative Protein Adsorption Test, the antibacterial adhesion test method can be found in Performance Test (2) Antibacterial Adhesion, and the antiplatelet adhesion test method can be found in Performance Test (3) Antiplatelet Adhesion.
[0044] As shown in Table 3, compared with Comparative Example 1, the relative protein adsorption of the sample in Example 3 was significantly reduced, proving that the mixed ion polymer coating was successfully modified to the material surface, showing good resistance to non-specific protein adsorption. Among them, the best anti-non-specific protein adsorption effect was achieved when the plasma was treated for 90 seconds.
[0045] Table 3 Sample test results of Example 3 and Comparative Example 1
[0046] sample Plasma treatment time (s) Relative protein adsorption (%) Sample 10 30 11.6 Sample 11 60 7.79 Sample 12 90 6.99 Sample 13 120 7.45 Comparative Example 1 / 100
[0047] from Figure 2 It can be seen that compared with Example 1, the number of Escherichia coli adsorbed on the sample surface of Example 3 is significantly reduced, proving that the mixed ion polymer coating is stably bonded to the surface of the substrate and exerts excellent anti-bacterial adhesion ability.
[0048] Figure 3 It shows that platelets adhere and activate on Comparative Example 1, leading to thrombosis. The sample of Example 3 effectively inhibits platelet adhesion and thrombosis. Therefore, the prepared mixed ion polymer coating can resist nonspecific protein adsorption in plasma, thereby effectively reducing platelet adhesion and activation, indicating that the mixed ion polymer coating prepared based on PECVD has a high degree of blood compatibility.
[0049] Example 4
[0050] The polyurethane film was ultrasonically cleaned with ethanol and deionized water for 15 min and dried at 60 °C for 90 min. After the material was placed in the reaction chamber, nitrogen was bubbled through the methyl acrylate and N, N-dimethylallylamine mixture cooled in an ice-water bath at a flow rate of 0.01 m / min, 0.3 m / min, and 1.8 m / min to carry the monomers into the reaction chamber. 2 The membrane was treated at a power of 90 s to initiate grafting and polymerization of monomers on the membrane surface, and then washed with ethanol and deionized water for 15 min, hydrolyzed with a saturated sodium chloride solution containing 0.1 mol / L sodium hydroxide at 37°C for 3 h, washed with deionized water after the hydrolysis, and dried at room temperature for 27 h.
[0051] The relative protein adsorption test method is shown in performance test (1) relative protein adsorption test.
[0052] As shown in Table 4, compared with Comparative Example 1, the relative protein adsorption amount of the sample in Example 4 is significantly reduced, proving that the mixed ion polymer coating is successfully modified to the material surface and exhibits good resistance to nonspecific protein adsorption.
[0053] Table 4 Sample test results of Example 4 and Comparative Example 1
[0054]
[0055]
[0056] Example 5
[0057] The polyurethane film was ultrasonically cleaned with ethanol and deionized water for 15 min and dried at 60 °C for 90 min. After the material was placed in the reaction chamber, nitrogen was bubbled through a mixture of methyl acrylate and N, N-dimethylallylamine cooled in an ice-water bath to carry the monomers into the reaction chamber. 2 The membrane was treated at 400 W for 90 s to initiate the grafting and polymerization of monomers on the membrane surface, and then washed with ethanol and deionized water for 15 min. The membrane was hydrolyzed with 0.1 mol / L hydrochloric acid solution for 3 h, 0.1 mol / L sodium bicarbonate solution overnight, saturated sodium carbonate solution overnight, and saturated sodium chloride solution containing 0.1 mol / L sodium hydroxide at 37 ° C for 3 h. After the hydrolysis, the membrane was washed with deionized water and dried at room temperature for 27 h.
[0058] The relative protein adsorption test method is shown in performance test (1) relative protein adsorption test.
[0059] As shown in Table 5, compared with Comparative Example 1, the relative protein adsorption of the sample in Example 5 is significantly reduced, proving that the mixed ion polymer coating is successfully modified to the surface of the material, showing good resistance to non-specific protein adsorption. Among them, when hydrolyzed with a saturated sodium chloride solution containing 0.1 mol / L sodium hydroxide, the resistance to non-specific protein adsorption is the strongest.
[0060] Table 5 Sample test results of Example 5 and Comparative Example 1
[0061] sample Hydrolysis solution Relative protein adsorption (%) Sample 17 hydrochloric acid 12.8 Sample 18 Sodium bicarbonate 24.1 Sample 19 Sodium carbonate 7.18 Sample 20 Sodium hydroxide and saturated sodium chloride 6.99 Comparative Example 1 / 100
[0062] Example 6
[0063] The polyurethane and nylon membranes were ultrasonically cleaned with ethanol and deionized water for 15 min and dried at 60 °C for 90 min. After the materials were placed in the reaction chamber, nitrogen was bubbled through a mixture of methyl acrylate and N, N-dimethylallylamine cooled in an ice-water bath to carry the monomers into the reaction chamber. 2 The membrane was treated at 400 W for 90 s to initiate the grafting and polymerization of monomers on the membrane surface, and then washed with ethanol and deionized water for 15 min. The membrane was hydrolyzed with 0.1 mol / L hydrochloric acid solution for 3 h, 0.1 mol / L sodium bicarbonate solution overnight, saturated sodium carbonate solution overnight, and saturated sodium chloride solution containing 0.1 mol / L sodium hydroxide at 37 ° C for 3 h. After the hydrolysis, the membrane was washed with deionized water and dried at room temperature for 27 h.
[0064] The relative protein adsorption test method is shown in performance test (1) relative protein adsorption test.
[0065] As shown in Table 6, compared with Comparative Examples 1 and 2, the relative protein adsorption of the sample in Example 6 was significantly reduced, proving that the mixed ion polymer coating was successfully modified to the material surface and exhibited good resistance to nonspecific protein adsorption.
[0066] Table 6 Sample test results of Example 6 and Comparative Example 1
[0067] sample Base material Relative protein adsorption (%) Sample 21 Polyurethane 6.99 Comparative Example 1 Polyurethane 100 Sample 22 nylon 10.2 Comparative Example 2 nylon 73.5
[0068] Comparative Example 1
[0069] The polyurethane film was ultrasonically cleaned with ethanol and deionized water for 15 minutes and dried at 60°C for 90 minutes.
[0070] Comparative Example 2
[0071] The nylon membrane was ultrasonically cleaned with ethanol and deionized water for 15 minutes and dried at 60°C for 90 minutes.
[0072] Performance Test:
[0073] 1. Relative protein adsorption test
[0074] Fibrinogen was selected to perform protein adsorption test on the samples of Example and Comparative Example 1-2, and the method was as follows: a disc with a diameter of 1 cm was taken out from the samples of Example 1-6 and Comparative Example 1-2 with a hole puncher and placed in a 48-well plate. Weigh a number of solid fibrinogens, dissolve them with 1X PBS solution, prepare a 0.2 mg / mL solution, add 500 μL to each well, and incubate at 37°C for 75 min. Discard the supernatant, rinse with 1X PBS solution 5 times, remove the PBS solution, add 600 μL of blocking solution to each well, and block at 37°C for 1 h. Dilute HRP-labeled goat anti-human fibrinogen IgG 1:1000 into 1X PBS and shake well. Discard the supernatant in the well plate, add 500 μL of the diluted antibody solution, and incubate at 37°C for 30 min. Discard the supernatant, rinse with 1X PBS solution 5 times, add 500μL TMB colorimetric solution to each well, color at 37℃ for 15min, positive result is blue. Add 500μL 1mol / L hydrochloric acid to each well to stop, the solution turns yellow, measure the OD value at 450nm and 620nm with a microplate reader, and subtract the OD value at 620nm from the OD value at 450nm as the final OD value.
[0075] Relative protein adsorption = OD 实施例 / OD 对比例 ×100%
[0076] 2. Anti-bacterial adhesion
[0077] Use an analytical balance to weigh 2.50g of sodium chloride, 1.25g of yeast extract and 2.50g of tryptone. Add pure water to fully dissolve and adjust pH=7.40, then use a 250mL volumetric flask to make up the volume. The sample was divided and sterilized at 121°C for 30 minutes in a pressure steam sterilizer to obtain a sterilized LB medium. Take 5uL of the preserved Escherichia coli culture and inoculate it in 6mL of sterilized LB medium. Then place it in a horizontal shaker at 37°C and 220rpm and incubate overnight. Note that the inoculation operation must be performed on a clean workbench 1-2cm away from the alcohol lamp to ensure that the operating environment is strictly sterile. Take 1mL of the overnight cultured bacterial solution + 1mL of culture medium and add it to the well plate, and put in the material sheet. Then place it in a horizontal shaker at 37°C and 220rpm and culture for 6h. Example 3 and Control Example 1 were washed 5 times with PBS and fixed with 4% paraformaldehyde solution. After fixation, the fixative was washed away with PBS, and the samples were stained with propidium iodide solution for 30 minutes in the dark, and finally the stain was washed away with deionized water. The bacterial adsorption on the sample surface was observed with a fluorescence microscope.
[0078] 3. Antiplatelet Adhesion
[0079] Platelet-rich plasma was selected to perform platelet adhesion test on the samples of Example 3 and Comparative Example 1. Blood donated by healthy volunteers was centrifuged at 1000 rpm for 10 minutes to obtain platelet-rich plasma (PRP). The samples of Example 3 and Comparative Example 1 were punched to obtain discs with a diameter of 0.5 cm, which were placed in a 96-well plate and incubated with 0.1 ml PRP at 37°C for 2 hours. The samples were washed three times with PBS and the supernatant was discarded. Fix with 2.5% glutaraldehyde solution at 4°C for 45 minutes. The samples were washed three times with PBS, dried with an ethanol gradient, and freeze-dried in a freeze dryer. The platelet adhesion on the sample surface was observed using a scanning electron microscope.
[0080] The above embodiments are used to illustrate the present invention rather than to limit the present invention. Any modification and change made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.
Claims
1. A method for preparing a coating that resists nonspecific protein adsorption based on atmospheric pressure low temperature plasma enhanced chemical vapor deposition technology, characterized in that: The method uses organic monomers that provide positive and negative charges as raw materials, and adopts a normal pressure low-temperature plasma process to initiate free radicalization of the organic monomers, which are then polymerized on the surface of the substrate material, and then activated and cleaned to obtain a protein-resistant nonspecific adsorption coating.
2. According to claim 1, a method for preparing a coating resistant to nonspecific protein adsorption based on atmospheric pressure low temperature plasma enhanced chemical vapor deposition technology, the method comprises the following process steps: 1) Clean the base material to be coated; 2) preparing an organic monomer solution containing allyl ester and allyl amine and charging it into a storage bottle; 3) using compressed carrier gas to bubble through a storage bottle containing an organic monomer solution to carry the monomer to a reaction chamber containing a substrate material; 4) Turn on the plasma power supply, adjust the voltage and gas flow, use the electric field to plasmatize the carrier gas and monomer, and diffuse them to the surface to form a polymer film; 5) hydrolyzing the ester groups on the surface of the polymer membrane, then drying it with clean compressed air, and washing it with pure water to obtain a coating that resists nonspecific protein adsorption.
3. The method for preparing a coating resistant to nonspecific protein adsorption based on atmospheric pressure low temperature plasma enhanced chemical vapor deposition technology according to claim 1, characterized in that: The base material is a water-insoluble polyurethane or nylon polymer material containing amide groups. The base material is ultrasonically cleaned and dried with ethanol and ultrapure water respectively, and / or cleaned with oxygen and nitrogen plasma.
4. The method for preparing a coating resistant to nonspecific protein adsorption based on atmospheric pressure low temperature plasma enhanced chemical vapor deposition technology according to claim 1, characterized in that: The monomers for preparing the mixed ion polymer layer are carried by a compressed carrier gas, which is nitrogen and / or argon.
5. The method for preparing a coating resistant to nonspecific protein adsorption based on atmospheric pressure low temperature plasma enhanced chemical vapor deposition technology according to claim 2, characterized in that: The two monomers containing allyl ester and allyl amine are mixed in a certain ratio. Allyl ester and allyl amine are organic monomers that provide negative charge and positive charge respectively, so that the surface has uniformly mixed positive and negative charges, and the amount of positive and negative charges is basically the same; the allyl ester is one or more of methyl acrylate, tert-butyl acrylate or methyl methacrylate; the allyl amine is one or more of N,N-dimethylacrylamine, N-methylacrylamine or acrylamine.
6. The method for preparing a coating resistant to nonspecific protein adsorption based on atmospheric pressure low temperature plasma enhanced chemical vapor deposition technology according to claim 2, characterized in that: The allyl-containing ester is methyl acrylate, the allyl-containing amine is N,N-dimethylacrylamine, and the volume ratio of the former to the latter is 1:1 to 3:1 when nitrogen is used as a carrier gas. The storage bottle containing the organic monomer solution is immersed in an ice water bath.
7. The method for preparing a coating resistant to nonspecific protein adsorption based on atmospheric pressure low temperature plasma enhanced chemical vapor deposition technology according to claim 5, characterized in that: The plasma treatment power is 0.2W / cm 2 -0.8W / cm 2 , the processing time is 30-120s.
8. The method for preparing a coating resistant to nonspecific protein adsorption based on atmospheric pressure low temperature plasma enhanced chemical vapor deposition technology according to claim 1, characterized in that: After plasma treatment, the substrate material was washed with ethanol to remove unfixed monomers and oligomers.
9. The method for preparing a coating resistant to nonspecific protein adsorption based on atmospheric pressure low temperature plasma enhanced chemical vapor deposition technology according to claim 1, characterized in that: The hydrolysis is carried out by using an inorganic strong acid or alkali, wherein the inorganic strong acid includes hydrochloric acid or sulfuric acid, and the inorganic alkali includes at least one of a sodium bicarbonate solution, a sodium carbonate solution and a sodium hydroxide solution.
10. Application of an anti-nonspecific protein adsorption coating based on atmospheric pressure low-temperature plasma enhanced chemical vapor deposition technology in medical devices that come into contact with blood and tissues.
Citation Information
Patent Citations
Polyurethane material with protein adsorption resistance and cell adhesion resistance and preparing method thereof
CN104262668A
Anti-protein adsorbing coating modified base material and preparation method thereof
CN113402754A
Anti-fouling and wear-resistant hydrophilic lubricating coating grafted on surface of medical apparatus and preparation method of anti-fouling and wear-resistant hydrophilic lubricating coating
CN115814172A
Method of preparing a macromolecule deterrent surface on a pharmaceutical package
US20070187280A1